MEDIA, SEKSUALITAS PEREMPUAN DAN PORNOGRAFI DALAM DOMINASI PARTRIARKHI - ., Nuraina (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2011)
This writing explores how the role of media in influencing the perspective or perception of society and government on the issue of pornography. This situation raised in the middle of the issues the need for laws that regulate pornography and porno-action which then becomes a debate between the groups in society. But unfortunately, the debates were never rooted on media issues as part of the emergence of perceptions of media and pornography, as well as parthiarki domination of women in it. This is the bottom line of this paper.